Numerical Study on Plate Holders Pipe Recovery Boiler Superheater - Amrinsyah Amrinsyah; amir syam; Darianto Darianto; zulfikar zulfikar (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2018)
The important part which has a function as supporting of superheater header on the boiler recovery type (RB) is a couple of support plate which is hanged on the hanger rod. This part is very difficult to analyze by experimental because there are in a tight insulation and heavy duty condition. This research aim to obtain the stress distribution that happened on the plate as the effect of static load in simulation mode. The model is designed base on the dimension of real support plate size 400x200 mm and thickness 15 mm. It is use the FEM software of Ansys version 5.4. The theory of failure analysis of Tresca and von Mises become the reference for materials strength. The area contact theory of b represents the reference to determine the length of stress area along curve of both contact area. The material that is used is from steel ASTM A514 with the yield strength 690 MPa. The Result is stress distribution along curve and also critical point which has possibility failure occurs on the support plate. The analysis result could be a reference for the development of the further construction.